Kajian Etnobotani Ginaru (Bubur Tradisional) Etnis Batak Phakpak di Sumatera Utara - Marina Silalahi; Endang C. Purba; Yunita RMB Sitompul; Giovani Hutabarat (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Porridge is one of the processed foods made from rice, which varies relatively from one region to another. The Batak Phakpak ethnic group in North Sumatra has wisdom in making traditional porridge known as ginaru. This research aims to explain the ethnobotanical study of ginaru as a traditional porridge. The research method was carried out using an ethnobotanical approach using interviews and observations. Data analysis was carried out qualitatively by explaining the role of plants in making ginaru. Ginaru is a traditional Batak Phakpak porridge that can be made with the main ingredients of groats (a by-product of the rice milling process) or rice and cassava (Manihot esculenta). The pulp is brownish yellow in color, has a distinctive aroma, and is rich in nutrients. A total of 15 species from 11 families and 13 genera of plants are used to make ginaru. As many as 40% of the plants used as spices in making ginaru are rich in essential oils and have anti-microbial activity. Andaliman (Zanthoxylum acanthopodium) and galugur acid (Garcinia atroviridis) are typical Sumatrean spices that have great potential to be developed as natural food preservatives.